Effect of Grape Seed Extract on the Physicochemical and Sensory Properties of Chicken Nuggets - Kaur, Simranjeet; Kumar, Sunil; Bhat, Z.F. (Journal of Meat Science, 2015)
The present study was designed to evaluate the possibility of utilization of grape seed extract in the development of designer chicken nuggets. The products were developed by incorporating different levels of grape seed extract (0.1%, 0.2%, and 0.3%) and were analyzed for various physicochemical and sensory parameters. A significant (p<0.05) effect of grape seed extract was observed on the pH and moisture content of the chicken nuggets. The grape seed extract significantly (p<0.05) improved various sensory attributes of the products. A significant (p<0.05) increase was observed in colour and appearance, flavour, juiciness and overall acceptability of nuggets incorporated with grape seed extract. Thus, chicken nuggets of good to very good acceptability could be prepared by incorporating grape seed extract up to 0.3% level in the formulation.